The meaning of work for a diverse group of women in higher education institutions - Mayer, Claude-Hélène; Surtee, Sabie; May, Michelle S. (South African Journal of Higher Education, 2016)
The construction of meaning at work impacts on individual, psychological and work related outcomes. The meaning of work, however, in the context of women leaders working in higher education institutions (HEIs) has not yet been comprehensively researched and understood in South Africa and internationally. This article explores the perspectives on meaning of work for women leaders working in HEIs in South Africa and internationally. With regard to meaning at work, limited research exists on HEIs in South Africa and internationally. This needs to be explored in-depth from emic female perspectives to contribute to both to the benefit of women in HEIs and to the transformation goals of organisations. Data from a qualitative research study within the phenomenological paradigm are presented. The research methods include the collection and analysis of 29 in-depth interviews with South African and international women leaders working in academic and administrative positions in HEIs. The findings show that women leaders in HEIs connect meaningfulness to five main categories namely, career, life values, spirituality, race and gender identity. HEIs need to focus more on the construction of meaningfulness at work for women leaders to cater for empowering working conditions.This article contributes to the dearth in literature on meaningfulness at work for women leaders within HEIs. It also provides conclusions and recommendations.